An Audit of the Use of Renal Function Tests among Paediatric Mortalities (2016)
Background: Acute kidney injury is a frequent and serious complication encountered in critically ill children and is an independent risk factor for mortality. Major causes of childhood mortality in our environment are conditions frequently complicated by kidney failure, yet kidney failure is conspicuously absent in many of the reports. The actual proportion of these critically ill children subjected to renal function tests is not known. In view of the low representation of kidney failure as a cause of mortality in our environment, we sought to know what proportion of critically ill/dying patients had renal functions tests done and to identify any cases of missed diagnosis. Methods: This was a descriptive study of the mortalities in the Department of Paediatrics, University College Hospital, Ibadan, between August 2004 and May 2006, particularly those due to kidney failure. Data from the departmental mortality database collected on a weekly basis were analyzed. Results: Out of 4,941 admissions, there were 542 mortalities (age 1day -13 years) giving a mortality rate of 11%. Low birth weight, malaria, severe perinatal asphyxia, meningitis and neonatal tetanus were the leading five causes of death. Over 80% of the mortalities were under-fives